الاحتراق التعلمي وعلاقته بالتسويف الأكاديمي لدى طلاب كلية التربية بجامعة سوهاج في ضوء متغيري النوع الاجتماعي والتخصص الدراسي - عبداللاه، عبدالرسول عبدالباقي عبداللطيف (جامعة سوهاج - كلية التربية, 2017)
هدفت الدراسة الحالية إلى بحث العلاقات بين والاحتراق التعلمي ببعديه (عدم المشاركة، والاستنفاد) والتسويف الأكاديمي، ودراسة تأثير متغيري النوع الاجتماعي والتخصص الأكاديمي على هذين المتغيرين، وإمكانية التنبؤ بالتسويف الأكاديمي من خلال بعدي عدم المشاركة والاستنفاد لدى عينة من طلاب كلية التربية بجامعة سوهاج قوامها (380) طالباً وطالبة من الجنسين (110 ذكور، 270 إناث) من تخصصات أكاديمية مختلفة (107 شعب علمية، 273 شعب أدبية)، وقد تراوحت أعمار العينة ما بين (20-23.92 سنة)، بمتوسط عمري مقداره (21.95) وانحراف معياري مقداره (0.65)، وقد تم جمع بيانات الدراسة باستخدام قائمة أولدنبرج للاحتراق التعلمي (تعريب/ الباحث) ومقياس التسويف الأكاديمي (إعداد/ معاوية أبوغزال)، وقد أظهرت نتائج معامل الارتباط عن وجود علاقة موجبة ودالة إحصائيا بين الاحتراق التعلمي ببعديه (عدم المشاركة والاستنفاد)، والتسويف الأكاديمي. وأظهرت نتائج تحليل التباين الثنائي وجود تأثير دال إحصائياً (0.05) لمتغير النوع الاجتماعي على أداء عينة الدراسة على بعد الاستنفاد، وجود تأثير دال إحصائيا عند مستوي (0.05) لمتغير التخصص الأكاديمي (علمي-أدبي) على الأداء قائمة الاحتراق الأكاديمي ككل وبعديها (عدم المشاركة، والاستنفاد)، في حين لا يوجد تأثير دال إحصائياً لمتغير النوع الاجتماعي على الأداء على قائمة الاحتراق الأكاديمي ككل وبعد عدم المشاركة، كما أنه لا يوجد تأثير دال إحصائياً لتفاعل متغيري النوع الاجتماعي والتخصص الأكاديمي على أداء عينة الدراسة على قائمة الاحتراق الأكاديمي ككل وبعديها (عدم المشاركة، والاستنفاد). وقد كشفت نتائج تحليل الانحدار المتعدد عن أن بعدي الاحتراق الأكاديمي (عدم المشاركة، الاستنفاد) يتنبأون بالتسويف الأكاديمي. ومن خلال نتائج الدراسة تم تقديم بعض التوصيات والمقترحات.
The current study aimed at investigating the relationship between the disengagement and exhaustion dimensions of learning burnout and academic procrastination, and the effect of gender (male - female), academic major (scientific - literary), and the interaction between them on the students' performance on Oldenburg Inventory for learning burnout (translated by the reseaher) and the Academic Procrastination Scale (Aboughazale, 2012). As well, the possibility of predicting students' academic procrastination scores from their scores on disengagement and exhaustion dimensions of learning burnout was also investigated. The participants of the study included 380 students (110 males, 270 females) enrolled in different academic majors (107 scientific, 273 literary) at the Faculty of Education in the Sohag University, Egypt. The ages of respondents ranged from 20 to 23.92 with average age level of 21.95 years and standard deviation of (0.65). Results as indicated by correlation coefficients show that the academic procrastination was positively correlated with disengagement and exhaustion dimensions of learning burnout. The results from the two-way ANOVA analysis revealed that there was a statistically significant effect of gender (male - female) on the performance of the study sample on exhaustion dimension. There was a statistically significant effect of academic major (scientific- literary) in the performance of the sample on disengagement and exhaustion dimensions of learning burnout. Yet, there was no statistically significant effect of gender (male - female), and the interaction between gender and major on the sample's performance on the disengagement dimension of the learning burnout inventory. As well, there was no statistically significant effect of the interaction between gender and academic major on the sample's performace on the learning burnout inventory. Similarly, results of the two-way ANOVA analysis revealed that there was no statistically significant effect of gender (male - female) and academic major (scientific- literary), and the interaction between them on their performance in academic procrastination. The results of multiple linear regression analysis revealed that disengagement and exhaustion dimensions of learning burnout can statistically predict students' academic procrastination score. Based on the results of the study, some recommendations as well as suggestions for furthr research were proposed.
Keywords: التسويف الأكاديمي -- التخصصات الأكاديمية -- طلبة الجامعات -- جامعة سوهاج -- الاحتراق التعلمي